2008
DOI: 10.1021/om8002043
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally Efficient Unsymmetrical Ruthenium(II) NNN Complex Catalysts Bearing a Pyridyl-Based Pyrazolyl−Imidazolyl Ligand for Transfer Hydrogenation of Ketones

Abstract: Rare ruthenium(II) complexes bearing a pyridylbased pyrazolyl-imidazolyl ligand were synthesized and exhibited exceptionally high catalytic actiVity in the transfer hydrogenation of ketones in 2-propanol at 82 °C or room temperature, reaching 100% conVersion of the substrates and final TOFs up to 7.2 × 10 5 h -1 with 0.05 mol % catalyst at 82 °C and 55 800 h -1 with 0.1 mol % catalyst at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 52 publications
(19 reference statements)
4
64
0
Order By: Relevance
“…Typical for octahedral ruthenium(II) monophosphane complexes, the 31 P NMR resonances of 3a,b are observed a δ = 44.20 and 42.71 ppm. [18] We recently published the reaction of the N,N,N-ligand 1b (see Scheme 1), with N-H instead of N-allyl functions, with [RuCl 2 (PPh 3 ) 3 ]. [19] This leads to a cationic ruthenium(II) complex of the type [RuCl(1b)(PPh 3 ) 2 ]Cl with the two phosphane ligands trans to each other ( 31 P NMR: δ = 25.5 ppm).…”
Section: Synthesis and Characterization Of Ligands And Complexesmentioning
confidence: 99%
“…Typical for octahedral ruthenium(II) monophosphane complexes, the 31 P NMR resonances of 3a,b are observed a δ = 44.20 and 42.71 ppm. [18] We recently published the reaction of the N,N,N-ligand 1b (see Scheme 1), with N-H instead of N-allyl functions, with [RuCl 2 (PPh 3 ) 3 ]. [19] This leads to a cationic ruthenium(II) complex of the type [RuCl(1b)(PPh 3 ) 2 ]Cl with the two phosphane ligands trans to each other ( 31 P NMR: δ = 25.5 ppm).…”
Section: Synthesis and Characterization Of Ligands And Complexesmentioning
confidence: 99%
“…As the bulkiness of the substituents decreased from bromo to chloro, the resultant enantioselectivity decreased from 95% to 93% (entries 4 and 5, Table 3). We have previously shown that a benzimidazolyl N-H in a ligand can accelerate the TH and ATH of ketones [28][29][30], and an imidazolinyl N-H functionality has also been reported as improving the enantioselectivity in ATH [38]. In our case, the combination of the two N-H functionalities may provide the complex catalysts with high catalytic activity and good selectivity for ATH of ketones under mild conditions.…”
Section: Asymmetric Transfer Hydrogenation Of Ketonesmentioning
confidence: 62%
“…Following the procedure previously reported from our laboratory [21][22][23][24][25][26][27][28][29][30][31][32], complex 6a was tested as a catalyst for the transfer hydrogenation of acetophenone in the presence of i-PrOK. To our surprise, 6a exhibited excellent catalytic activity for the reduction of acetophenone in 2-propanol even at room temperature (28 °C).…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the commonly used reduction processes which involve high hydrogen pressure or hazardous reducing reagents [2][3][4], transfer hydrogenation has emerged as a safe, ecofriendly and versatile tool for the reduction of carbonyl compounds. Recently, the Ru(II) complexes bearing planar tridentate N 3 ligands and unsymmetrical planar tridentate ligands have been successfully developed and explored to construct the effective catalyst systems for the transfer hydrogenation of ketones [5][6][7][8][9][10]. In the study of the transfer hydrogenation mechanism, several ruthenium hydride complexes are considered as active species [11][12][13][14][15][16][17][18], but some ruthenium hydride complexes, such as RuHCl(PPh 3 ) 3 [11], are not the really active species.…”
mentioning
confidence: 99%